Pengaruh Terpaan Hashtag #OOTD Pada Media Sosial TikTok Terhadap Perilaku Impulse Buying (Survei pada Pengikut Akun X @callistaverss) - Rasya, Muhammad Irfan Hady; Lubis, Fardiah Oktariani; Oxcygentri, Oky (Peneliti.net, 2024)
This research aims to examine and measure the impact of #OOTD on impulse buying behavior among followers of the X account @callistaverss. This research uses a questionnaire to answer statements. The population in this study were followers of the X account @callistaverss. The sample in this study was 99 respondents. The sampling technique in this research uses a non-probability sampling technique using a purposive sampling method, with the following criteria: 1) Active followers on the X account @callistaverss, 2) Using the TikTok social media account, 3) Have you ever seen content with the hashtag #OOTD on TikTok social media. The data collection technique in this research uses a questionnaire in the form of a Google Form. The analysis techniques in this research use validity tests, reliability tests, normality tests, coefficient of determination tests, simple linear regression tests, and hypothesis tests. The results of the research show that there is a significant influence between #OOTD exposure on Tiktok social media on impulse buying behavior among followers of the X account @callistaverss.